Probing doubly charged Higgs bosons in e(+)e(-) colliders at the ILC and the CLIC in a 3-3-1 model - Cieza Montalvo, J. E.; Cortez, Nelson V.; Tonasse, M. D. [UNESP] (Amer Physical Soc, 2008)
The SU(3)(L) circle times U(1)(N) electroweak model predicts new Higgs bosons beyond the one of the standard model. In this work we investigate the signature and production of doubly charged Higgs bosons in the e(+)e(-) International Linear Collider and in the CERN Linear Collider. We compute the branching ratios for the doubly charged gauge bosons of the model.